Creating 'resilience imaginaries' for city-regional planning. Issue 4 (3rd April 2023) - Pitidis, Vangelis; Coaffee, Jon; Bouikidis, Aphrodite
ABSTRACT: Resilience narratives have gathered increased attention in city-regional planning over the last two decades, emphasizing holistic foresight, long-term strategic visioning, cross-sectoral integration and collaborative modes of planning. Combining such resilience narratives with the established idea of socio-spatial imaginaries, we introduce the novel concept of 'resilience imaginaries' and explore its application in the city-region of Thessaloniki, Greece. This paper illustrates that resilience imaginaries can be viewed as dynamic and politically contested visions for long-term city-regional development, collectively structured by civic stakeholders, institutionally expressed through city-regional governance transformations and materially manifested through city-regional planning interventions.